Labour mobility and labour market adjustment in the EU - Alfonso Arpaia; Aron Kiss; Balazs Palvolgyi; Alessandro Turrini (IZA Journal of Migration, 2016)
This paper assesses the role of labour mobility in the adjustment to asymmetric economic shocks in the EU. After presenting a series of stylised facts of mobility in the EU, it assesses mobility as a channel of economic adjustment by means of a vector autoregression (VAR) analysis in the vein of Blanchard and Katz (BPEA 1:1-75, 1992). Results indicate that, over the period 1970-2013, mobility absorbed about a quarter of an asymmetric shock within 1 year. Movements in response to shocks have almost doubled since the introduction of the euro. In contrast to previous papers on the labour market adjustment in the EU, the response of wages is integrated to the analysis. It is found that real wages have also become more responsive to asymmetric shocks.
Keywords: J61; J64; 330; Labour mobility; Geographic mobility; Migration; Adjustment; Asymmetric shocks; Optimal currency areas; European Union